1995
DOI: 10.1073/pnas.92.10.4621
|View full text |Cite
|
Sign up to set email alerts
|

Bridging grafts and transient nerve growth factor infusions promote long-term central nervous system neuronal rescue and partial functional recovery.

Abstract: Grafts of favorable axonal growth substrates were combined with transient nerve growth factor (NGF) infusions to promote morphological and functional recovery in the adult rat brain after lesions of the septohippocampal projection. Long-term septal cholinergic neuronal rescue and partial hippocampal reinnervation were achieved, resulting in partial functional recovery on a simple task assessing habituation but not on a more complex task assessing spatial reference memory. Control Neurons of the adult mamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(37 citation statements)
references
References 32 publications
(37 reference statements)
1
34
0
2
Order By: Relevance
“…Similarly, regrowth was promoted by treatment with proteases that degrade chondroitin sulfate proteoglycans (Bradbury et al, 2002;Rudge and Silver, 1990). Other approaches aimed at promoting recovery of CNS axons have been based on modification of the environment by local transplantation of embryonic tissue (Grady et al, 1985), Schwann cells (Xu et al, 1997), or cells that provide a source of trophic factors to increase the survival rate of the cell bodies (Coumans et al, 2001;Tuszynski and Gage, 1995).…”
Section: Macrophages and Microglia In Central Nervous System Injury: mentioning
confidence: 99%
“…Similarly, regrowth was promoted by treatment with proteases that degrade chondroitin sulfate proteoglycans (Bradbury et al, 2002;Rudge and Silver, 1990). Other approaches aimed at promoting recovery of CNS axons have been based on modification of the environment by local transplantation of embryonic tissue (Grady et al, 1985), Schwann cells (Xu et al, 1997), or cells that provide a source of trophic factors to increase the survival rate of the cell bodies (Coumans et al, 2001;Tuszynski and Gage, 1995).…”
Section: Macrophages and Microglia In Central Nervous System Injury: mentioning
confidence: 99%
“…This is highly feasible due to the high degree of plasticity demonstrated by cholinergic terminals. Following axotomy, cholinergic axons reestablish normal innervation patterns in the cerebral cortex (Farris et al, 1993), and NGF modulates the reestablishment of cholinergic ®bers and behavioral function recovery (Farris et al, 1995;Tuszynski and Gage, 1995). NGF also increases the number of varicosities, or possible release sites, along the cholinergic axon (Garofalo et al, 1993;Farris et al, 1995).…”
Section: Altered Dendritic Structure and Companion Axonal Changementioning
confidence: 99%
“…[1][2][3]47 NGF increases ChAT activity both in vitro 32,48 and in intact animals. 8,49 Also, intraparenchymal grafts of cells genetically modified to produce NGF can prevent cholinergic neuronal degeneration caused by fornix transection 50,51 or by immunolesioning procedures. 52 Recent studies have shown that administration of exogenous neurotrophic factors can reduce spatial memory deficits in rats following TBI.…”
Section: Figure 2 Ngf Gene Transfectio In Vitro (A) Increases In Ngfmentioning
confidence: 99%